Nanostructured alumina as seed protectant against three stored-product insect pests. (May 2020) - Belhamel, Chiraz; Boulekbache–Makhlouf, Lila; Bedini, Stefano; Tani, Camilla; Lombardi, Tiziana; Giannotti, Paolo; Madani, Khodir; Belhamel, Kamel; Conti, Barbara
Abstract: Nanoparticles represent a promising technology to enhance the efficacy of bioactive materials and a large number of studies showed the effectiveness of nanostructured materials against various arthropod species of economic importance. In this work nanostructured alumina (NSA) was prepared using sol-gel method and the effect of NSA was evaluated as seed protectant against the main seed-infesting insect pests Oryzaephilus surinamensis (L.) (Coleoptera: Silvanidae) Stegobium paniceum (L.) (Coleoptera: Anobiidae), and Tribolium confusum Jacquelin du Val (Coleoptera: Tenebrionidae). Besides, we tested the effects of NSA on seed germination and plant growth and finally, we assessed the presence of NSA as a contaminant in the leaves of bean plants germinated from NSA-treated seeds. The results showed significant insecticidal activity of NSA against the three tested species. After sixteen days, the percentage of insect mortality at the highest NSA concentration tested (400 mg kg −1 ) was 100.00% for S. paniceum followed by O. surinamensis (80.64%) and T . confusum (79.41%). Besides, in-vitro tests indicated that NSA has no effects on seeds germination and on radicle and shoot elongation. No effects of NSA were also observed in pot tests on the bean's plants. No differences were recorded in the leaves area, stoma density and roots length. On the contrary, the shoot of plants from NSA-treated beans was about 66% higher than the one of the non-treated plants (shoot, 15.07 cm for the control and 22.76 cm for NSA-treated plants). Finally, no contamination by alumina particles was found by EDX-system coupled with Scanning Electron Microscopy (SEM) on the surface of the P. vulgaris leaves obtained from NSA-treated beans. Overall, the results showed that NSA could be an effective protective agent for the control insect pests during the seeds storage. Highlights: Nanostructured alumina was obtained by sol-gel method. Nanostructured alumina exerted insecticidal activity against seeds-infesting insect pests. Nanostructured alumina do not affect germination of bean seeds nor root and shoot elongation. Nanostructured alumina do not affect the growth of bean plants in pot culture.